Identification of clam plasma proteins that bind its pathogen Quahog Parasite Unknown. Issue 77 (June 2018) - Hartman, Rachel; Pales Espinosa, Emmanuelle; Allam, Bassem
Abstract: The hard clam ( Mercenaria mercenaria ) is among the most economically-important marine species along the east coast of the United States, representing the first marine resource in several Northeastern states. The species is rather resilient to infections and the only important disease of hard clams results from an infection caused by Quahog Parasite Unknown (QPX), a protistan parasite that can lead to significant mortality events in wild and aquacultured clam stocks. Though the presence of QPX disease has been documented since the 1960s, little information is available on cellular and molecular interactions between the parasite and the host. This study examined the interactions between the clam immune system and QPX cells. First, the effect of clam plasma on the binding of hemocytes to parasite cells was evaluated. Second, clam plasma proteins that bind QPX cells were identified through proteomic (LC-MS/MS) analyses. Finally, the effect of prior clam exposure to QPX on the abundance of QPX-reactive proteins in the plasma was evaluated. Results showed that plasma factors enhance the attachment of hemocytes to QPX. Among the proteins that specifically bind to QPX cells, several lectins were identified, as well as complement component proteins and proteolytic enzymes. Furthermore, results showed that some of these lectins and complement-related proteins are inducible as their abundance significantly increased following QPX challenge. These results shed light on plasma proteins involved in the recognition and binding of parasite cells and provide molecular targets for future investigations of factors involved in clam resistance to the disease, and ultimately for the selection of resistant clam stocks. Graphical abstract: Image 1 Highlights: Interactions between clam plasma proteins and QPX were investigated. Clam plasma proteins enhance hemocyte attachment to QPX cells. Plasma proteins that bind QPX include C-type lectins and complement components. Some of these proteins are inducible and increase following QPX challenge.